Jeanne-Agnès Bado, - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
director of a small enterprise in local construction materials in Ouagadougou, Burkina Faso You either have or you don t have money to start off with, but one thing is sure: it s easier to get finance if you know your rights, can draw up a...